Laser fabricated tungsten oxide surface for solar energy harvesting and dust effects - Yilbas, Bekir S.; Ali, Haider; Al-Sharafi, Abdullah; Karatas, C. (Elsevier BV, 2019)
Abstract Laser gas assisted texturing of tungsten surface is carried out towards achieving increased solar absorption at the surface. Morphological and metallurgical changes at the textured surface are examined using the analytical tools. Hydrophobic characteristics of the surface are assessed incorporating the water droplet contact angle measurement technique. The influence of environmental dust on the laser textured surface is investigated mimicking the humid air ambient. The adhesion of the dry mud on the textured surface is determined through measurement of tangential forces required to remove the dry mud from the surface. It is found that laser gas assisted processing results in surface texture composing of micro/nano pillars and formation of WO3 compounds in the treated layer. Hydrophobicity of the surface improves significantly after the laser texturing; in which case, the water droplet contact angle increases from 64° to 94°. The dry mud and dried liquid solution residues influence the UV visible absorption of the laser textured surface. In this case, absorption reduces almost 20% because of scattering of incident UV visible radiation by the residues at the textured surface.
Keywords: 7. Clean energy